Corporate Insolvency Procedures and Bank Behavior : A Study of Selected Asian Economies - Hussain, Qaizar; Wihlborg, Clas. (Washington, D.C. : International Monetary Fund, 1999)
This paper explores insolvency and debt recovery procedures, and political, legal, and institutional factors influencing financial decisions of corporations and banks during pre-crisis years in six Asian economies. It also examines whether these factors may have contributed to the depth and duration of the 1997 crisis. There are two key findings: First, bank behavior and other institutional factors, and not the nature of stakeholder orientation, seem to explain variations in capital structures and the depth of recessions across economies. Second, aspects of insolvency procedures favoring rehabilitation of 'financially distressed' firms seem to explain well the expected duration of the crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet